DAMPAK HARGA DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN ULANG JILBAB PADA OUTLET RABBANI COLLECTION DI BOJONEGORO - AROFATU ZAHRO, WINDA (Jurnal Pendidikan Tata Niaga (JPTN), 2016)
The purpose of research is to reveal how big the Repuchase and brand imagetowards decision of Repuchase for Veil in Outlet Rabbani Collection in Bojonegoro. Kind of research used is descriptive research with quantitative method. Technique of sampling applies nonprobability sampling with technique of Accidental sampling. Research sampling used is eighty three of respondent participation. Hypothesis examining is done by using experiment F and T. The result of data analysis acquired indicates that the condition of price and brand image toward decision of repurchase for Jilbab in Outlet Rabbani Collection in Bojonegoro is good and powerful. Key words: Price, Brand Image, Repurchase